Modified pedicle screw–rod fixation as a minimally invasive treatment for anterior pelvic ring injuries: an initial case series - Xiaotian Wu; Zuoqing Liu; Wenqin Fu; Shan Zhao; Juntao Feng (Journal of Orthopaedic Surgery and Research, 2017)
Abstract Background Unstable pelvic ring injuries often involve high mortality and morbidity. This study was aimed to evaluate the modified minimally invasive pedicle screw–rod fixation for anterior pelvic ring injuries, in the respects of its feasibility, merits, and limitations. Methods Twenty-three patients with unstable pelvic ring injuries underwent the modified anterior pedicle screw–rod fixation, with or without posterior fixation. The clinical outcomes were assessed using Majeed scores, and the quality of reduction was evaluated according to the criteria of Matta. Results Majeed scores showed that the clinical outcomes at postoperatively 1 year were excellent in 14 patients, good in 7, and fair in 2. One woman complained of persistent pain at the pubic tubercle during sexual intercourse. Iatrogenic neuropraxia of the unilateral lateral femoral cutaneous nerve occurred in 3 patients. Unilateral femoral nerve palsy occurred in 1 patient. The reduction was found to be excellent in 12 patients, good in 8, and fair in 3. Heterotopic ossification occurred in 8 patients, all being asymptomatic. Conclusions The modified pedicle screw–rod fixation with the minimally invasive technique offered an effective alternative for unstable anterior pelvic ring injuries.